Alternative Expression Pattern of MALT1-A20-NF-κB in Patients with Rheumatoid Arthritis - Xu Wang; Lihua Zhu; Ziwei Liao; Fan Zhang; Ling Xu; Yan Xu; Shaohua Chen; Lijian Yang; Yi Zhou; Yangqiu Li (Journal of Immunology Research)
Rheumatoid arthritis (RA) is an inflammatory autoimmune disorder; abnormal T cell immunity plays a critical role in the development of RA. Recently, A20 was identified as a key negative regulator for T cell activation and inflammatory signaling and may be involved in RA pathogenesis. In this study, we analyzed the expression level of A20, NF-κB, and A20 regulatory factor mucosa-associated lymphoid tissue lymphoma translocation gene 1 (MALT1) in patients with RA. Real-time PCR was used to determine the expression level of MALT1, MALT-V1, A20, and NF-κB genes in RA and healthy individuals (HI). Significantly lower A20 expression was found in RA patients compared with those in the healthy group, while NF-κB overexpression could be detected in patients with RA. Moreover, the MALT1 and MALT1-V1 expression level was downregulated in RA patients. A positive correlation between MALT1 and A20 and MALT1-V1 and A20 was found in patients with RA, and a tendency towards a negative correlation was found between MALT1 and NF-κB, MALT1-V1 and NF-κB, and A20 and NF-κB. In conclusion, we first characterized the alternative expression pattern of MALT1, A20, and NF-κB in RA, which may be related to abnormal T cell activation.